NUMERICAL ABUNDANCE OF BENTHIC MACROINVERTEBRATES IN SELECTED RESERVOIRS OF TAMIL NADU - Manoharan, S; MURUGESAN, V K; Palaniswamy, Rani (Journal of the Inland Fisheries Society of India, 2016)
Richness and diversity of benthic macroinvertebrates in nineteen reservoirs located at different river basins of TamilÂ Nadu were investigated. Krishnagiri reservoir recorded the highest macrobenthic population (4290 u/m2) followed by Willington (4170 u/m2). Gunderipallam, Varattupallam, Amaravathy, Uppar, Vaigai, Pechiparai and Vidur reservoirs alsoÂ recorded large quantity of macrobenthos (1926 to 2338 u/m2). Palar-Poranthalar, Pilloor, Vembakottai, Manimuthar andÂ Orathupalayam exhibited a moderate quantity of macrobenthos (952 to 1458 u/m2). A low level of bottom fauna wasÂ encountered at Parambikulam (502 u/m2), Thoonakadavu (838 u/m2), Peruvaripallam (329 u/m2), Uppar (411 u/m2) andÂ Odathurai (364 u/m2). While Chironomus larvae formed the major portion of the macrobenthos (2835 u/m2) at Krishnagiri, molluscan forms dominated (3939 u/m2) at Willington reservoir.